Minimizing microbial contamination risk simultaneously from multiple hospital washbasins by automated cleaning and disinfection of U-bends with electrochemically activated solutions. Issue 3 (November 2018) - Deasy, E.C.; Moloney, E.M.; Boyle, M.A.; Swan, J.S.; Geoghegan, D.A.; Brennan, G.I.; Fleming, T.E.; O'Donnell, M.J.; Coleman, D.C.
Summary: Background: Outbreaks of infection associated with microbial biofilm in hospital hand washbasin U-bends are being reported increasingly. In a previous study, the efficacy of a prototype automated U-bend decontamination method was demonstrated for a single non-hospital pattern washbasin. It used two electrochemically activated solutions (ECA) generated from brine: catholyte with detergent properties and anolyte with disinfectant properties. Aim: To develop and test a large-scale automated ECA treatment system to decontaminate 10 hospital pattern washbasin U-bends simultaneously in a busy hospital clinic. Methods: A programmable system was developed whereby the washbasin drain outlets, U-bends and proximal wastewater pipework automatically underwent 10-min treatments with catholyte followed by anolyte, three times weekly, over five months. Six untreated washbasins served as controls. Quantitative bacterial counts from U-bends were determined on Columbia blood agar, Reasoner's 2A agar and Pseudomonas aeruginosa selective agar following treatment and 24 h later. Findings: The average bacterial densities in colony-forming units/swab from treated U-bends showed a >3 log reduction compared with controls, and reductions were highly significant ( P <0.0001) on all media. There was no significant increase in average bacterial counts from treated U-bends 24 h later on all media ( P >0.1). P. aeruginosa was the most prevalent organism recovered throughout the study. Internal examination of untreated U-bends using electron microscopy showed dense biofilm extending to the washbasin drain outlet junction, whereas treated U-bends were free from biofilm. Conclusion: Simultaneous automated treatment of multiple hospital washbasin U-bends with ECA consistently minimizes microbial contamination and thus the associated risk of infection.